Enhanced proangiogenic potential of mesenchymal stem cell-derived exosomes stimulated by a nitric oxide releasing polymer - Du, Wei; Zhang, Kaiyue; Zhang, Shuaiqiang; Wang, Ran; Nie, Yan; Tao, Hongyan; Han, Zhibo; Liang, Lu; Wang, Di; Liu, Jianfeng; Liu, Na; Han, Zhongchao; et al. (Biomaterials, 2017)
Mesenchymal stem cell (MSC)-derived exosomes have been recognized as new candidates for the treatment of degenerative diseases or injury and may provide an alternative to cell-based therapy. However, the compositions in MSC-derived exosomes are highly influenced by the microenvironment in which their original cells reside. Here, we hypothesized that a nitric oxide (NO)-releasing polymer can boost the proangiogenic compositions of exosomes and enhance their proangiogenic capacity. Our results demonstrated that exosomes, released from human placenta-derived MSCs (hP-MSCs) by NO stimulation, augment the angiogenic effects of human umbilical vein endothelial cells (HUVECs) in vitro. Moreover, exosomes released from hP-MSCs by NO stimulation revealed superior angiogenic effects and ameliorated limb function in a murine model of hind limb ischemia. Further analysis demonstrated that increased VEGF and miR-126 levels in exosomes released from hP-MSCs by NO stimulation were identified as a novel mechanism contributing to the increased capacity of these exosomes to promote angiogenic processes. In conclusion, designing specific microenvironments for in vitro stem cell culture, such as those containing bioactive material, will facilitate the development of customized exosomes encapsulating a beneficial composition of stem cells for cell-free therapeutic applications.